THE ROLE OF LITERARY TRANSLATION IN SHAPING LITERARY AND CULTURAL SPACE AND CONSTRUCTING NATIONAL IDENTITY - Tetiana Liashenko (Іноземна філологія)
The article analyses the role of literary translation in the shaping of literary and cultural space and construction of national identity. The research is carried out in line with the Cultural Studies approach in Translation Studies, according to which literary translation is interpreted not as a purely linguistic phenomenon, but primarily as a refl ection of a cultural tradition, a kind of projection of events of historical, nation-building and nationwide dimensions. In particular, the author explains the need to rethink certain concepts and methodological approaches in Translation Studies due to the dynamic interpretation of borders and rethinking of the concept of identity. An attempt is made to identify the essential aspects of literary translation as a form of interliterary interaction and intercultural communication. The paper illustrates the distinction of the nation-building function of literary translation in Ukrainian Translation Studies. The interrelationships between literary translation, culture and national identity are established. The polysphere model of cultural space is outlined. Varieties of national identity are considered. The author characterizes literary translation as an important practice of forming a national cultural space as a process of creation, dissemination and consumption of such cultural texts as translated literature. Translators are participants in intercultural communication, they create translations and facilitate their dissemination and reception in various public spheres from the global to the niche levels around various generating centres. A cultural centre-generator whose identity is in line with the national identity of the country and which makes deliberate efforts to ensure that its discursive identity is shared by the entire public sphere contributes to the formation and strengthening of the national identity of its audience. The problem of the unity and integrity of the national cultural space is caused by the cultural compatibility of all its public spheres, an important factor of which is the use of language as a cultural code. The spread of electronic global communication and the growing trend towards the use of a global language reduces the presence of the national language in the global communication space, which leads to the levelling of national identities. In such circumstances, high quality translation will help preserve the national identity of the cultural space.